New tables for the complete solution of Ganguillet and Kutter's formula for the flow of liquid in open channels, pipes, sewers, and conduits in two parts - Moore, E. C. S. (B.T. Batsford, 1901)
Part 1 is arranged for 1080 inclinations from 1 over 1, to 1 over 21,120 for 15 different values of (n); Part 2 is for use with all other values of (n).